2019
DOI: 10.1002/jbm.b.34351
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of honey‐doped electrospun scaffolds to delay wound closure

Abstract: Manuka honey is an ancient remedy to improve wound healing; however, an effective delivery system is needed to facilitate extended release of honey into wounds. We developed an electrospun dermal regeneration template consisting of a poly (ε‐caprolactone) (PCL) scaffold embedded with 1%, 5%, 10%, or 20% manuka honey. In vitro studies demonstrated that honey PCL scaffolds were not toxic to macrophages, and they allowed for macrophage infiltration into the scaffolds. Vascular endothelial growth factor (VEGF), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…9,40 MH is a natural debriding agent by eliminating wound odor and has analgesic effects. 40 Beside methylglyoxal, MH consists mainly of carbohydrates (sugars) and water, but it contains also minor amounts of proteins, lysozyme, minerals, enzymes, phenolic acids, amino acids, vitamins and organic acids. 41,42 These substances offer another very important feature of MH, its antibacterial and antibiofilm efficiency.…”
mentioning
confidence: 99%
“…9,40 MH is a natural debriding agent by eliminating wound odor and has analgesic effects. 40 Beside methylglyoxal, MH consists mainly of carbohydrates (sugars) and water, but it contains also minor amounts of proteins, lysozyme, minerals, enzymes, phenolic acids, amino acids, vitamins and organic acids. 41,42 These substances offer another very important feature of MH, its antibacterial and antibiofilm efficiency.…”
mentioning
confidence: 99%
“…Notably, new blood vessels were formed in the new bone tissues. It was reported that sufficient vascularization could improve the bone regeneration by providing nourishment for the bone defects (Hilliard et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies have already incorporated natural products into polymeric systems for wound dressings applications, including membranes, hydrogels and scaffolds. [44][45][46] Extracts rich in sugars or polysaccharides can act by stimulating the angiogenesis process, which accelerates the wound healing. [47][48][49] Furthermore, topical treatment of wounds with sugars promotes the nutrition of the skin and reduces inflammation, as well stimulates the process of re-epithelialization of the injured tissue.…”
Section: Evaluation Of Wound Healing Properties Of the Formulationsmentioning
confidence: 99%